Economics of milk production in Pune district of Maharashtra: A comparative analysis - G, Athare P; Verma, Ajay; Malhotra, R; R, Sendhil (Indian Journal of Dairy Science, 2020)
The study of economics of milk production is an important base to determine the profitability of dairy farming. The information was collected from 80 members and 80 non-members of dairy cooperatives from Pune district of Maharashtra in 2018-19. The average net maintenance cost per animal per day was more for members as compared to non-members in case of crossbred and local cow, where as in case of buffalo it was more for non-members as compared to members. Per litre cost of milk production for crossbred cow, buffalo and local cow was observed more for member group as compared to non-member group. The feed and fodder accounted major share in total variable cost followed by labour cost for both group. Further, it was found the return per litre from milk production was more for members as compared to non-members in case of crossbred cow. Whereas in case of buffalo, return per litre from milk production was more for non-members than members due to non-members are selling milk directly to the consumers and getting more price. In case of local cow, net return per litre of milk production worked out to be negative for both members and non-members due to low productivity and there is need increase the productivity by adopting scientific dairy farming practices.